PERAN ORGANISATION OF ISLAMIC COOPERATION DALAM KRISIS KEMANUSIAAN AFGHANISTAN TAHUN 2021–2023 - Ryantori, Ryantori; Fahlevi, Reza Budi (Moestopo Journal of International Relations (MJIR), 2023)
Afghanistan has experienced a prolonged armed conflict, resulting in a worsening humanitarian crisis marked by food insecurity, women’s rights restrictions, and disruption of formal education. This situation deteriorated further after the Taliban regained control in 2021, a regime not fully recognized by the international community. The Organisation of Islamic Cooperation (OIC), as a major international organization representing 57 Muslim-majority countries, responded by adopting the Resolution on the Humanitarian Situation in Afghanistan. In its implementation, the OIC established a Humanitarian Trust Fund through the Islamic Development Bank, sent a delegation of scholars to address women’s issues, mandated the Islamic Organisation for Food Security (IOFS) to coordinate food-related initiatives, issued political warnings regarding terrorism, and established a permanent OIC office in Kabul. The OIC's approach prioritized peaceful mechanisms such as mediation, negotiation, and multilateral coordination, seeking a collective response to resolve Afghanistan’s humanitarian crisis. This research employs a qualitative descriptive method with a case study approach to examine the OIC’s role. The findings reveal that the OIC actively fulfills its function as an international organization through institutional mechanisms and diplomacy to contribute to a peaceful and prosperous Afghanistan.